Serum Zinc Level in Children Suffering from Type 1 Diabetes Mellitus and Its Relationship with Glycemic Control: An Experience from A Tertiary Level Specialized Diabetic Hospital in Bangladesh - Haque, Shawana; Mozaffor, Miliva; Mahmud, Md Mostaque; Muttalib, MA (Community Based Medical Journal, 2022)
A cross-sectional study was conducted in the Department of Biochemistry and Molecular Biology of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka, Bangladesh, between July 2016 and June 2017, to evaluate serum zinc level and its relationship with glycemic control in type 1 diabetic children. A total of 160 participants (all aged between 1 and 18 years) were selected from the outpatient department (OPD) of BIRDEM General Hospital-2, Dhaka – 80 type 1 diabetic children as cases and 80 apparently healthy children as controls. We measured anthropometric parameters all study subjects. Serum zinc level was assessed using colorimetric method. Fasting plasma glucose level was estimated using enzymatic glucose-oxidase method. Glycemic control was evaluated through estimation of HbA1c using a high-performance liquid chromatographic method. The mean serum zinc levels were significantly lower in patient with type 1 DM compared to control (72.5±16.5 vs. 82.4±13.3 μg/dl; P<0.001). Lower levels of zinc were found in subjects with poor glycemic control compared to good glycemic control (62.8±14.6 vs. 78.8±14.6 μg/dl; P<0.001). Moreover, serum zinc levels were significantly lower in patients who have duration of diabetes mellitus for 5 years or more (P<0.05). To summarize, serum zinc level is lower in type 1 diabetic children in comparison to its healthy counterpart and this lower zinc level is strongly associated with poor glycemic control which may potentially contribute to the early development of diabetic complications in children. CBMJ 2022 July: vol. 11 no. 02 P: 80-85